2016
DOI: 10.1177/0033354916662212
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Risk-Based and Birth-Cohort Strategies for Identifying Hepatitis C Virus Infection Among People Entering Prison, Wisconsin, 2014

Abstract: Objectives. The prevalence of hepatitis C virus (HCV) infection among young adults is rising in Wisconsin. We examined the prevalence of HCV infection among male and female inmates entering two Wisconsin prisons and evaluated existing and alternate risk-based strategies for identifying HCV infection at intake.Methods. We added HCV testing to the intake procedures for all 1,239 adults prison entrants at the Wisconsin Department of Corrections (WDOC) from November 3, 2014, to January 31, 2015. We identified risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 15 publications
1
18
0
Order By: Relevance
“…This disparity has been shown previously, (18) and these estimates suggest racial disparities in hepatitis C have not declined since 2010. Higher prevalence among non-Hispanic blacks compared with persons of other race/ethnicities likely stems from a combination of factors including lower rates of acute hepatitis C clearance, (26)(27)(28) higher rates of incarceration, (29)(30)(31)(32)(33) and less access to effective treatment services. (34)(35)(36) Clinical evidence suggested that interferon-based therapies were less effective for treating genotype 1 HCV infection among non-Hispanic black versus persons of other race/ethnicities, but newer direct-acting antiviral medications provide equally effective treatment across racial groups.…”
Section: Discussionmentioning
confidence: 99%
“…This disparity has been shown previously, (18) and these estimates suggest racial disparities in hepatitis C have not declined since 2010. Higher prevalence among non-Hispanic blacks compared with persons of other race/ethnicities likely stems from a combination of factors including lower rates of acute hepatitis C clearance, (26)(27)(28) higher rates of incarceration, (29)(30)(31)(32)(33) and less access to effective treatment services. (34)(35)(36) Clinical evidence suggested that interferon-based therapies were less effective for treating genotype 1 HCV infection among non-Hispanic black versus persons of other race/ethnicities, but newer direct-acting antiviral medications provide equally effective treatment across racial groups.…”
Section: Discussionmentioning
confidence: 99%
“…While the choice of a screening strategy is highly in uenced by the expected prevalence and budget priorities, evidence on the different HCV screening approaches in low-and middle-income countries is scarce (18,22). In resource-limited settings, risked-based screening is postulated to be of value for case nding among target populations (7,19). However, the reliability of self-reported risk behaviors and the consistency with which the screening criteria are applied have shown to limit the early case detection ability (19,23).…”
Section: Discussionmentioning
confidence: 99%
“…In resource-limited settings, risked-based screening is postulated to be of value for case nding among target populations (7,19). However, the reliability of self-reported risk behaviors and the consistency with which the screening criteria are applied have shown to limit the early case detection ability (19,23). Studies on the e cacy of a risk-based HCV strategy among marginalized populations are limited, and to date, case nding by surveys have been only done in high-income countries (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,5 The current findings are different from that of a study at the Wisconsin Department of Corrections. 24 The latter found that a targeted approach using history of injection drug use and history of liver disease identified 92% of cases. Using the WADOC data set, a targeted approach including history of drugs use and elevated liver function tests would only identify 58% of cases diagnosed with routine testing.…”
Section: Discussionmentioning
confidence: 99%